Static deformation due to two-dimensional seismic sources embedded in an isotropic half-space in smooth contact with an orthotropic half-space - Godara, Yogita; Sahrawat, Ravinder Kumar; Singh, Mahabir (Global Journal of Mathematical Analysis, 2014)
Closed form analytical expressions for displacements and stresses at any point of a two-phase medium consisting of a homogeneous, isotropic, perfectly elastic half-space in smooth contact with a homogeneous, orthotropic, perfectly elastic half-space caused by two-dimensional seismic sources located in the isotropic half-space are obtained. The method consists of first finding the integral expressions for two half-spaces in smooth contact from the corresponding expressions for an unbounded medium by applying suitable boundary conditions at the interface and then evaluating the integrals analytically. Here, we discuss the horizontal and vertical displacements for vertical dip-slip fault numerically. Numerical computations indicate that the deformation field due to a source in an isotropic half-space in smooth contact with an anisotropic half-space may differ substantially from the deformation field when both the half-spaces are isotropic. Keywords: Isotropic Half-Space, Orthotropic Half-Space, Static-Deformation, Smooth Contact.